Oral vancomycin prophylaxis during systemic antibiotic exposure to prevent Clostridiodes difficile infection relapses. (29th April 2019) - Caroff, Daniel A.; Menchaca, John T.; Zhang, Zilu; Rhee, Chanu; Calderwood, Michael S.; Kubiak, David W.; Yokoe, Deborah S.; Klompas, Michael
Abstract: Objective: To determine whether oral vancomycin prophylaxis accompanying systemic antibiotics reduces the risk of relapse in patients with history of Clostridioides difficile infection (CDI). Design: Retrospective cohort study. Patients: Adult inpatients with a history of CDI who received systemic antibiotics in either of 2 hospitals between January 2009 and June 2015. Methods: We compared relapse rates in patients who started oral vancomycin concurrently with systemic antibiotics (exposed group) versus those who did not. We assessed for CDI relapse by toxin or nucleic acid testing at 90 days. We used inverse probability weighting and machine learning to adjust for confounders, to estimate propensity for treatment, and to calculate odds ratios for CDI relapse. We performed secondary analyses limited to toxin-positive relapses, patients with 1 versus >1 prior CDI episodes, and patients who received oral vancomycin on each antibiotic day. Results: CDI relapse occurred within 90 days in 19 of 193 exposed patients (9.8%) versus 53 of 567 unexposed patients (9.4%; unadjusted odds ratio [OR], 1.06; 95% confidence interval [CI], 0.60–1.81; adjusted OR, 0.63; 95% CI, 0.35–1.14). CDI relapses at 90 days were less frequent in exposed patients with only 1 prior episode of CDI (OR, 0.42; 95% CI, 0.19–0.93) but not in those with >1 prior episode (OR, 1.19; 95% CI, 0.42–3.33). Our findings were consistent with a lack of benefit of oral vancomycin when restricting results to toxin-positive relapses and to patients who received vancomycin each antibiotic day. Conclusions: Prophylactic oral vancomycin was not consistently associated with reduced risk of CDI relapse among hospitalized patients receiving systemic antibiotics. However, patients with only 1 prior CDI episode may benefit.